PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS TPACK DALAM MENINGKATKAN LITERASI DIGITAL DAN SELF - EFFICACY SISWA - Gultom, Lasria Sari; Fauzi, Muhammad Amin; Syafwatul, Rif’aat; Syahril (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study aims to develop learning devices using the Problem-Based Learning (PBL) model based on Technological, Pedagogical, and Content Knowledge (TPACK) to enhance students' digital literacy and self-efficacy in a valid, practical, and effective manner. The developed learning devices consist of lesson plans (RPP) and student worksheets (LKPD). This development research employs the IDI (Instructional Development Institute) model, which includes three stages: 1. Define, 2. Design, 3. Develop. The research instruments include validation sheets, practicality assessment sheets by teachers and students, learning implementation observation sheets, and test instruments for digital literacy and self-efficacy. The trial subjects are teachers and sixth-grade students of SD Swasta Kartini Handayani Pematangsiantar. The research data were analyzed to determine the quality category of the developed learning devices. The data analysis is divided into three criteria:1. Validity analysis of learning devices, 2. Practicality analysis of learning devices, 3. Effectiveness analysis of learning devices. The learning devices are considered valid if expert assessments of the lesson plans (RPP) and student worksheets (LKPD) meet the "good" criteria, and the digital literacy and self-efficacy test instruments are declared valid based on expert judgment. The practicality criteria are met if teachers' and students' assessments fall into the "good" category. Meanwhile, the learning devices are considered effective if the learning mastery exceeds 60%. Data collection was conducted through observations, tests, and interviews. The research results indicate that the developed learning devices are valid, practical, and effective in improving students' digital literacy and self-efficacy. This study contributes to innovative learning strategies that support student-centered education in the digital era.